The English Pronouns and Their Usage - Egamnazarov Kobil Abdunazarovich (Genius Publishing Group, 2021)
This article highlights about the English Pronouns and their usages. The Pronoun, as we all know, is a word used in place of a noun. Over the years, the effective use of English Pronouns by the users has been observed by researchers as a problematic circumstance. In the study, the background issues surrounding the existence of Pronouns have been revealed; some types of Pronouns have been identified, explained and illustrated with copious example as well as the features of the Pronouns.
Keywords: Pronouns; features; types; parsing